Studi Islam dalam Pendekatan Sosiologi - Nashihin Nashihin; Muhyidin Muhyidin (JOSH: Journal of Sharia, 2023)
Religious truth is a transcendental truth, absolute truth. The presence of religion is required to be actively involved in regulating the course of life and to be able to solve various problems in society. If so then religion must be able to answer all the problems that arise. The problem is whether religious teachings will solve various problems if only studied with a normative theological approach? According to the writer's opinion, to understand religion, various other alternative approaches are needed, which operationally can provide answers to various problems that arise. The alternative approach includes a sociological approach. The importance of this sociological approach is given the many religious teachings related to social problems. In several verses of the Qur'an it is written an order to believe and then accompanied by an order to act righteously, as in Surah an-Nisa [4] verse 36 there is an order to worship Allah and a prohibition against associating partners with Him followed by an order to do good to both parents, close relatives, orphans, the poor, close neighbors and distant neighbors, colleagues and so on. The sociological approach has a very important role in trying to understand the meanings, symbols that can be found in religion. With this sociological approach, religion will be easy to understand and can be carried out easily too.